PEDAGOGICAL AND PSYCHOLOGICAL FEATURES OF PROFESSIONAL TRAINING OF TEACHERS OF PRE-SCHOOL EDUCATIONAL ORGANIZATIONS - Khushnazarova Mamura Nodirovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article covers the pedagogical and psychological features of professional training of pedagogical educators of future preschool education organizations, the problems of formation of specific personal qualities along with specific knowledge, skills, qualifications for each educational recipient in the educational process.